Inflation Uncertainty and Real Economic Activity: An Alternative Approach - Kantor, Laurence G. (The Review of Economics and Statistics, 1986)
A bstracct-Increased uncertainty about inflation is shown to encourage inflation hedging which, in turn, reduces the macroeconomic costs of that uncertainty. Portfolio theory and empirical evidence support the contention that only the portion of inflation volatility that cannot be hedged has real economic effects. Additional empinrcal results suggest that: (i) increased inflation volatility in the early seventies was eventually followed by portfolio reallocations that allowed for greatly improved inflation hedging, and (ii) the deletenrous effect of inflation uncertainty on real economic activity shown in previouis studies is significantly smaller after 1975.